Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/vaccines9060622
|View full text |Cite
|
Sign up to set email alerts
|

Flavivirus NS1 and Its Potential in Vaccine Development

Abstract: The Flavivirus genus contains many important human pathogens, including dengue, Japanese encephalitis (JE), tick-borne encephalitis (TBE), West Nile (WN), yellow fever (YF) and Zika (ZIK) viruses. While there are effective vaccines for a few flavivirus diseases (JE, TBE and YF), the majority do not have vaccines, including WN and ZIK. The flavivirus nonstructural 1 (NS1) protein has an unusual structure–function because it is glycosylated and forms different structures to facilitate different roles intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 137 publications
(137 reference statements)
2
54
0
Order By: Relevance
“…Mature NS1 is 352 amino acids long with an apparent molecular mass between 40 – 50 kDa depending on its glycosylation state at asparagine residues 130 and 207 for the majority of flaviviruses ( 4 ). All flavivirus NS1 species contain 12 conserved cysteine residues that form six intra-chain disulphide bonds, two at the N-terminus and four at the C-terminus, that are crucial for non-covalent dimer formation which remain stable to reduction but are heat-labile ( 5 ).…”
Section: Main Textmentioning
confidence: 99%
“…Mature NS1 is 352 amino acids long with an apparent molecular mass between 40 – 50 kDa depending on its glycosylation state at asparagine residues 130 and 207 for the majority of flaviviruses ( 4 ). All flavivirus NS1 species contain 12 conserved cysteine residues that form six intra-chain disulphide bonds, two at the N-terminus and four at the C-terminus, that are crucial for non-covalent dimer formation which remain stable to reduction but are heat-labile ( 5 ).…”
Section: Main Textmentioning
confidence: 99%
“…NS1 is secreted alongside dengue virus particles during an infection. It is a multifunctional protein which exists in different oligomeric forms intracellularly and extracellularly 5 , and they play distinctly different roles. The intracellular NS1 (iNS1), exists as membrane associated dimeric form and is a part of the viral replication complex.…”
Section: Mainmentioning
confidence: 99%
“…One aspect of this work is to define DENV NS1 epitopes targeted by DENV cross-reactive anti-NS1 antibodies derived from B-cell repertoires of dengue patients. Prior studies have identified several immunodominant epitopes located on the wing and C-terminal half of the β-ladder domains [ 37 ]. Biering et.al.…”
Section: Discussionmentioning
confidence: 99%
“…The functional basis of these domains is not thoroughly understood and target epitopes for antibody-mediated protection are not comprehensive. To date, several NS1 epitopes have been identified from naturally infected humans and immunized mice [ 36 , 37 ], but the functions of only a few have been demonstrated. Immuno-dominant regions of the NS1 protein associated with cell binding have been identified solely on the wing and the C-terminal end of the β-ladder domains [ 33 , 38 ].…”
Section: Introductionmentioning
confidence: 99%